Role of NOM molecular size on iodo-trihalomethane formation during chlorination and chloramination. (1st October 2016) - Zhang, Jie; Chen, Dan-Dan; Li, Lei; Li, Wen-Wei; Mu, Yang; Yu, Han-Qing
Abstract: Natural organic matter (NOM) is the major precursor for the generation of disinfection byproducts (DBPs) during disinfection, but the role of the NOM molecular size on the formation of iodinated DBPs (I-DBPs) is still unclear. The objective of this study was to evaluate the function of the NOM molecular size on the formation of iodo-trihalomethane (I-THMs) during chlorination and chloramination. Humic acid was adopted as the NOM matrix and fractionated into four molecular weight (MW) groups. Various parameters, including iodide, bromide, NOM concentrations, pH, and pre-chlorination time, were investigated for each MW fraction. During chlorination, high MW fractions (i.e., MW > 100 K Da and 50 K < MW < K00 K Da) produced more I-THMs compared with small MW fractions (i.e., MW < 3 K Da and 3 K < MW < 50 K Da). With the increase in the I − or NOM concentration, the formation of I-THMs increased for small MW fractions, while a slight reduction occurred for high MW fractions during chlorination. Higher pH resulted in more I-THM formation for small MW fractions, while the opposite was true for high MW fractions during chlorination. Compared to small MW fractions, bromide was relatively more reactive with high MW fractions in the formation of I-THMs during chlorination. During chloramination, the I-THM yields decreased with the increasing NOM concentration for high MW fractions. The concentration of bromine-containing I-THMs decreased with increasing pH for all MW fractions during chloramination. Additionally, with the prolongation of pre-chlorination time, the total amount of I-THMs decreased remarkably for MWs higher than 3 K Da, while a slight change for MW lower than 3 K Da occurred during chloramination. The results from this study suggest that the molecular weight of the NOM plays an important role in the formation of I-THMs during chlorination and chloramination. Highlights: More I-THMs were produced for the NOM with higher molecular weight. I −, NOM and pH positively affected I-THMs formation for small MW during chlorination. I − or NOM concentration negatively affected I-THMs formation during chloramination. Bromide was more reactive with high MW for I-THMs formation during chlorination. Pre-chlorination led to remarkable I-THMs decrease for MW > 3 K Da during chloramination.